Integrering av bioförgasningssystem i ett naturgaseldat kraftvärmeverk - Torell, Per (My University, 2003)
The purpose of this thesis is to examine how an integration of a biofuel based gasifier to an existing natural gas driven combined heat and power plant will affect the plants technical performance, economy and CO2-emissions. Biogas with low heating-value is mixed with the natural gas to be combusted in the gas turbine. Pressurised air-blown gasification with pellets as fuel is the reference-case to which all other process designs are compared. To the pressurised air-blown gasifier with pellets as fuel both a steam-dryer and a fluegas-dryer are integrated. Furthermore pressurised oxygen-blown and atmospheric gasification are analysed. The calculations are based on a planned natural gas based combined heat and power plant (about 300 MWel) which according to plan is to be constructed in Ryahamnen in Göteborg. The plant has been modelled in the simulation program GateCycle. Integration of the gasifier can be accomplished without any major modifications to the combined heat and power plant and depending on process design 27-51% can be mixed with the natural gas. The global CO2-emissions decrease for all cases. For pressurised air-blown gasification and pellets as fuel the global CO2-emissions decrease by 322 kton/year when 34% biogas is mixed with the natural gas and coal power is on the margin compared to operation with 100% natural gas. When a natural gas based combined heat and power plant is on the margin the CO2-emissions decrease by 264 kton/year. When a dryer is integrated the global CO2-emissions will increase as a result of decrease in efficiency. On the other hand the production costs for electricity are lower with a steam-dryer compared to pressurised gasification with pellets as fuel. With a steam-dryer the higher investment costs and the steam which is bled off to dry the biofuel is counterbalanced by lower fuel price. With a fluegas-dryer the production costs for electricity will be almost unchanged. The simulation for oxygen-blown and atmospheric gasification showed that the efficiency decreases due to the decrease in massflow through the gas turbine and the larger work done by the booster-compressors. Furthermore the global CO2-emissions increase as a consequence of the decreased efficiency. The economy for these two process designs have not been examined. It is not economically profitable to integrate a gasifier to a combined heat and power plant and there are possibly other solutions which has a lower cost for reducing CO2-emissions. The situation can change with a future trade of CO2-emission permits. The process designs which are most interesting for an integration of a gasifier for power and heat production are pressurised gasification with pellets as fuel or pressurised gasification with an integrated steam-dryer and wet biomass as fuel.
Keywords: Kemiteknik; Chemical Engineering